SOM neural network-based port function analysis: a case study in 21st-century Maritime Silk Road - Xie, Fahao; Zhang, Le; Zheng, Shanshui; Xu, Aijun; Li, Zhitao; Dai, Jiaxin; Xu, Lang (Frontiers in Marine Science, 2025)
The 21st-century Maritime Silk Road initiative by the Chinese government has garnered growing global attention. As pivotal facilitators of international trade, the maritime routes and ports along this route are attracting the interest of various stakeholders. There is a pressing need for extensive research to augment the existing theoretical frameworks. This paper introduces a Self-Organizing Map (SOM) neural network-based methodology for port function clustering, applied to 24 major ports spanning from the South China Sea to the ASEAN region in 2023. The clustering outcomes are cross-validated against port rankings derived from Principal Component Analysis. The study reveals several key insights: (1) Singapore Port, Hong Kong Port, Shenzhen Port, and Guangzhou Port emerge as the principal shipping hubs within the region; (2) The relationship between China and Singapore is identified as a linchpin for the sustainable development of the 21st-century Maritime Silk Road; (3) Guangdong Province is highlighted as a central economic and logistical node. Finally, the recommendations for the accelerated development of the Hainan Free Trade Port and Fujian Coastal Port is concluded.